2003
DOI: 10.1046/j.1365-2222.2003.01800.x
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships among asthma, atopy, rhinitis and exhaled nitric oxide in a population‐based sample of children

Abstract: SummaryBackground Exhaled nitric oxide (eNO) has attracted increasing interest as a non-invasive marker of airway inflammation in asthma. However, little evidence exists on the influences exerted on eNO by the interrelations among atopic status, asthma and rhinitis. Methods Among the 1156 children who participated in a large-scale epidemiological survey on asthma and allergies (ISAAC II: International Study of Asthma and Allergies in Childhood Phase II) in the city of Clermont-Ferrand, 53 asthmatics without co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
88
4
5

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 48 publications
17
88
4
5
Order By: Relevance
“…[2][3][4] However, other studies did not find a relation between atopy and eNO levels in children. 1,5,15 In particular, Latzin et al 15 failed to demonstrate a relation between atopy and eNO levels in 4-to 18-year-old healthy children. A possible explanation for these conflicting results might be found in the dimension of the studied sample, 5 the different prevalence of atopic children in the study samples, and the different age distributions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[2][3][4] However, other studies did not find a relation between atopy and eNO levels in children. 1,5,15 In particular, Latzin et al 15 failed to demonstrate a relation between atopy and eNO levels in 4-to 18-year-old healthy children. A possible explanation for these conflicting results might be found in the dimension of the studied sample, 5 the different prevalence of atopic children in the study samples, and the different age distributions.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with previous studies demonstrating the effect of the number of positive skin test results on the level of eNO. 1,2,4,7,22 In particular, Franklin et al 2 found that in healthy children eNO levels were higher in those with a positive skin prick test result and even higher in children with more than 1 positive skin test result, suggesting that allergen sensitization may play a significant role in elevating eNO production in the respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Esta herramienta se sustenta primariamente en las potenciales diferencias existentes entre población asmática y no asmática; además, recientemente también se han postulado diferencias según nivel de atopia. Diversos estudios han evaluado estas diferencias encontrándose, en general, un aumento en los niveles de ONe en suje-tos asmáticos, aunque también se han encontrado niveles elevados para sujetos atópicos y sobre todo sujetos asmáticos y atópicos [8][9][10][11][12][13][14][15] .…”
unclassified